UNIVERSAL EDUCATIONAL MATERIAL. EXHIBITION BY PER ISAK JUUSO FOR YOUTH AND CHILDREN - Griniuk, Marija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
This article explores the strategies employed by educators at the Sámi Center for Contemporary Art in Karasjok, Norway, in the production of educational materials related to an exhibition by Sámi duodji artist Per Isak Juuso. The study examines the process of creating materials that are suitable for various age groups of children and youth, and applicable to both local Sámi and international visitors. The research question is: How can the content of educational material within an art exhibition be designed to appeal to diverse audiences of children and youth? The aim of the study is to identify what kind of educational material about Sámi art can be used by different age groups and backgrounds, including local Sámi and international visitors. This aim is achieved through the following objectives: the design of educational material, presentation of the material to various groups of youth and children and their educators, evaluation of feedback on the content of the developed material, and a comparison, through observation, of the quantity of material used during the exhibition. The results of the research provide recommendations for art institutions and museums on how to develop universal educational materials that are suitable for various groups of learners and can be adapted by teachers to different levels of understanding during conversations.